Regional trajectories of entrepreneurship: The effect of socialism and transition - Michael Fritsch; Maria Kristalova; Michael Wyrwich (Friedrich Schiller University Jena, 2020)
We investigate how major historical shocks affect regional trajectories of economic activity. To this end, we conduct a comparative analysis of the development of entrepreneurship in East and West Germany after World War II. The introduction of an anti-entrepreneurial socialist economy in East Germany in 1949, and the subsequent transformation to a market economy four decades later were major historical shocks to the economy in general, and to entrepreneurship specifically. Our comparative analysis of East and West Germany assesses how these shocks affected the level of entrepreneurship at the regional level. Surprisingly, our results show that socialism does not have a long-run negative effect on the prevalence of self-employment in East Germany, despite the severe anti-entrepreneurial policies prevalent in Soviet-style socialism. Quite to the contrary, there is actually a positive treatment effect of German separation and reunification. Further analyses suggest that current structural differences in regional levels of self-employment in Germany are not pre-dominantly due to the socialist legacy of the East, but mainly a result of the shock transformation that occurred with reunification.
Keywords: L26; R11; N94; P25; 330; Entrepreneurship; self-employment; transition; socialism; regional development; GDR